Analysis of Mathematic Literacy Ability in Solving Problems in Arithmetic Sequences and Series based on Gender View - Rizky Mutiara Sari; Rita Pramujiyanti Khotimah (IKIP Mataram, 2023)
This study aims to describe the literacy ability of grade VIII students of SMP N 2 Plantungan in solving row and series problems reviewed from gender. The intended literacy skills are 1) communication skills, 2) mathematical skills, 3) problem-solving strategy skills, 4) symbol, formal, and technical language operation skills, and 5) reasoning and conclusion skills. The subjects of this study were one male student and one female student of grade VIII SMP N 2 Plantungan who were selected based on the highest score, and had good communication skills in solving the test questions that had been given. Research data sources from test results, interviews, and documentation. Data trianggualation is used to test the validity of data. This study showed that female students met all five literacy indicators tested, but male students only met four indicators of mathematical literacy ability. The thing that distinguishes this achievement is that male students have not fulfilled the ability to reason and reason. For the next research, you can conduct research on mathematical literacy skills with a focus on not many indicators so as to provide an in-depth description of the discussion.